Scientific Communication Perspectives in the New Digital Realities - López López, Wilson; Pontificia Universidad Javeriana (2009)
Academic communities tend to be conservative with regards to forms of scientific production and communication. It is clear that the format of scientific journals has not changed considerably in the past 50 years, and the APA guidelines that regulate the publication of articles in international Journals in Psychology has not had substantive changes. Transforming paper-based journals is, therefore, not an easy task. Nevertheless, the development of journals in the Internet faces us with new possibilities that enable a journal to overflow the traditional scope of communication directed only towards an expert community. The Internet allows researchers who publish in scientific journals to upload videos of their research, or interviews commenting their work. Journals can also create information for blogs, use tools such as RSS and Twitter to refine alert systems, and take advantage of information multiplication mechanisms through social networks such as Facebook. These tools are transforming the communication dynamics of journal editing teams. Editors and their teams, especially in the university context, need to address the challenge of incorporating these new ways of communicating information, with the complexities associated to each one. This must happen simultaneously with the task of taking care of the continuous improvement of processes that ensure editorial and content quality, visibility, accessibility, management, financing, and peer-recognition, since research communities ultimately consolidate citation networks that support this recognition. Because of that, Universitas Psychologica’s website is undergoing a learning process that involves the different teams in order for them to incorporate these new resources that we believe will enhance visibility, contribute to a clearer appropriation of knowledge, and we hope will contribute to the education of new researchers and to the use of this knowledge by non-expert communities. We invite you to read our Blog (http://universitaspsychologica.blogspot.com/), to follow us in Twitter (http://twitter.com/UniversitasPsyc), in Facebook (http://www.facebook.com/home.php#/group.php?gid=34631618744&ref=ts) and to watch our news channel in Youtube (http://www.youtube.com/user/UniversitasPsych). We hope that these and other channels we will be unveiling shortly, enable us to get closer to our readers. Last, but not least, I want to share the joy that the Public Knowledge Project (PKP) gave us by featuring our website as a model portal for the world. This is a recognition of years of work that has involved consolidating more and better ways of communication, and it is also an opportunity to insist that articles be submitted to the Journal by using PKP’s Open Journal System (OJS) platfor available in our website. If authors want more visibility for their contributions, they may send articles in English and Spanish, since the website can host both versions. We recommend authors and reviewers to take into consideration other articles published in this Journal or others from the Psicoredalyc System (http://redalyc.uaemex.mx/portales/areas/indices/psicologia/IndexPsicologia.jsp). As long as it is pertinent, this consideration will have an important weigh, since we are looking to boost the use of knowledge published by our journals. Wilson López-López Editor